Why Covid19 will not be gone soon: Lessons from the institutional economics of smallpox vaccination in 19th Century Germany - Katharina Muhlhoff (European Historical Economics Society (EHES), 2021)
Without safe and effective vaccination the current coronavirus pandemic will not get under control. Moreover, economic history suggests that even with vaccination, success is uncertain. To make this point, the present paper studies smallpox - an aggressive viral disease like Covid19 - as a model for future coronavirus immunization. Setting out from the formal basis of mathematical epidemiology and the theory of economic externalities, it finds that (i) vaccination externalities are non-monotonous in the burden of disease, that (ii) public interventions need to be tailored to the specific stages of the externality and (iii) that concrete implementation matters as much as formal institutions. To derive practical implications from these results, I retrace the prevention policies of two German states, Baden and Wurttemberg, which provide an intriguing natural experiment: Both featured similar socio-economic characteristics, both were initially ridden by smallpox and both passed mandatory vaccination laws at roughly the same time. But whereas laws hardly differed, one state - Baden - performed better in terms of epidemiological outcomes (smallpox prevalence and mortality), in cost efficiency and in measures of compliance. The main reasons for this success were the rapid implementation of mass vaccination, central coordination of vaccine supply, supervision and positive incentives for medical professionals. The bottom line of the historical case is therefore that governments which invest early in the infrastructural and personnel needs of a mass-vaccination system are likely rewarded by high popular acceptance and low disease prevalence.
Keywords: I12; I18; I38; N33; N43; 330; Health Externalities; Vaccination; Smallpox; Vaccine Resistance; Government Regulation; Historical Public Health Institutions